(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
The present study was conducted at the Artificial Insemination Center under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University and 3 selected regions of Mymensingh district (Bhabakhali, Boera and Douhakhula) to find out the reproductive performance of indigenous cows using Brahman cross-bred bull in a participatory breeding program. Semen characteristics of Brahman cross-bred breeding bulls were ejaculate volume, mass motility, sperm concentration and live sperm percentage were evaluated. A total of 1087 indigenous cows and four Brahman cross-bred breeding bulls (Bull ID ABG011, ABG012, ABG013 and ABG014) were used. Data on ejaculate volume, mass motility, sperm concentration and live sperm percentage of Brahman cross-bred breeding bulls were analyzed by SAS computer program. The pooled values of ejaculate volume, mass motility, sperm concentration and live sperm percentage were 4.00±0.06 ml, 69.19±0.29%, 1144.59±5.73 million/ml and 83.55±0.97%, respectively. The ejaculate volume, mass motility, sperm concentration and live sperm percentage were differed significantly (p<0.05) among the bulls in different seasons. Individual bull had significant (p<0.01) effect on the ejaculate volume, mass motility and sperm concentration. Season also had significant (p<0.01) effects on the ejaculate volume, mass motility, sperm concentration and live sperm percentage. Highest non-return rate (87.31%) was found on bull ABG012 in Bhabakhali where maximum conception rate (71.60%) was observed in Bhabakhali. The highest calving rate (96.29%) at second parity was obtained in Boera. Variations on ejaculate volume, mass motility, sperm concentration and live sperm percentage of Brahman cross-bred breeding bulls indicated that there is further scope to select breeding bull on the basis of semen production potential which would be use to upgrade indigenous cows for improving their beef production. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 173-181